The Sources of Economic Growth in Nigeria: A Growth Accounting Approach - Nkoro, Emeka; Uko, Aham Kelvin (European Journal of Economics and Business Studies, 2022)
The study investigated the sources of growth in Nigeria for the period 1960 to 2017 using the growth accounting framework of the standard neoclassical production function.Specifically, the study focused on evaluating the contribution of capital, labour and total factor productivity to economic growth in Nigeria. Additionally, in order to establish the relationship between capital, labour and total factor productivity, and economic growth, correlation coefficients between the variables were estimated. The results correlation analysis showed that the growths of capital, labour and total factor productivity were positively correlated with economic growth. Furthermore, the results from the growth accounting framework revealed that capital was found to be the major driver of economic growth in Nigeria during the entire period, 1961-2017. In the case of the sub-periods, capital was the major driver of economic growth in Nigeria during the first sub-period, 1961-1980. However, during the period, 1981-2000, labour was the major driver of economic growth, followed by capital while TFP growth contribution deteriorated as it was negative. Also, TFP was the major driver of economic growth during the period 2001-2017. Based on the foregoing, the study therefore recommends that, policies that encourage physical capital, human capital and technological development through domestic and foreign investments should be adopted, nurtured, sustained and intensified, noting that capital, human capital and technological development are key to economic growth and development.